Determinants of Successful E-Learning Implementation in Higher Education Institutions: A Cross-Institutional Student Perspective from Southern Africa - Vicente Antonio Halle; Luzaan Schlebusch (Universitas Majalengka, 2026)
Infrastructural and digital inequalities continue to undermine the effectiveness of e-learning in developing regions, creating a gap between positive student perceptions and actual system usage. This study adopts a quantitative, user-centric approach to investigate the determinants of successful e-learning implementation in Higher Education Institutions (HEIs) in Southern Africa, with particular focus on the usage paradox—the divergence between high acceptance and low sustained use. A cross-sectional survey was conducted with 92 students from two contrasting institutions in South Africa and Mozambique. Data were collected באמצעות a 5-point Likert scale questionnaire and analysed using descriptive statistics and chi-square (χ²) tests. The findings reveal a pronounced usage paradox: while perceived educational value is very high (94.6%), regular system use remains low (48.9%). A statistically significant relationship was found between institutional context and perceived success (χ²(1, N = 92) = 6.55, p = .01, Cramér’s V = 0.27). Key barriers include limited internet access and high data costs, highlighting the central role of infrastructural constraints. The study contributes to the literature by demonstrating that, in resource-constrained contexts, facilitating conditions may act as antecedent constraints rather than moderating factors. The proposed Structural Veto Model (SVM) is presented as a conceptual framework to explain this dynamic. The findings underscore the need for HEIs to prioritise equitable access and strengthen institutional support to enable sustained e-learning engagement.